Long-term results of irritable bowel syndrome treatment - A. I. Ulyanin; Yu. M. Poluektov; Ye. A. Poluektova; Ch. S. Pavlov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate duration of remission of irritable bowel syndrome after treatment by multistrain probiotic drug, motility regulator or antispasmodic medication. Material and methods. Original study included overall 87 patients with irritable bowel syndrome (IBS) or IBS in combination with functional dyspepsia (FD) in whom the diagnosis was confirmed according to compliance of symptoms to the Rome-III criteria and absence of organic diseases according to laboratory and instrumental investigation. In 42 patients diarrheapredominant variant of IBS was diagnosed (IBS-D), in 45 patients - constipation-predominant (IBS-C). All patients enrolled in original study underwent monotherapy by probiotic agent, motility regulator trimebutine or spasmolytic drug. The probiotic agent (Bifidobacterium bifidum, B. longum, B. infantis, Lactobacillus rhamnosus) was prescribed to 15 patients with IBS-D and 15 patients with IBS-C, motility regulator (trimebutine) - respectively to 12 and 15 patients, antispasmodic was used in 15 patients with IBS-D and 15 - with IBS-C. All patients at the end of 28thday of treatment achieved clinical remission of the disease (decrease of the total score of «7×7» Questionnaire for 50% and more). At the 30, 45 and 60 days after treatment secession in patients had telephone interview with health-related questions. Patients’ responses of those who received no maintenance therapy were statistically analyzed. Results. In 30 days secession of pharmaceutical therapy 73.3% of patients with IBS-D who received probiotic therapy during relapse maintained clinical remission, 75% of patients often motility regulator treatment and 60% of those who received antispasmodic medications. Of patients with IBS-C in 30 days after treatment termination remission was maintained in 60% of those after probiotic treatment, in 80% of the motility regulator treatment and in 60% antispasmodic therapy. In 45 days 47% of IBS-D patients treated by probiotics had sense of well-being, 58% of those who received motility regulators and 47% of patients who received antispasmodics previously. Of IBS-C patients in 1.5 months 33.3% of those, who received probiotic were symptomless, 46,3% of patients after trimebutine therapy and 33,3% of patients who achieved remission after antispasmodic therapy. In 60 days of IBS-D 20% in the group of patients remained in remission after probiotic treatment, 20% after trimebutine therapy and 33% after antispasmodic. Of IBS-C patients 20, 33 and 20% of patients respectively maintained clinical remission. No statistically significant differences between groups of patients with IBS-D and IBS-C were revealed (р>0.05). Conclusion. According to the obtained data, pharmacologically induced remission in the most of IBS cases is short-term. Remission duration depend neither on clinical variant of disease, nor on the group of drugs applied for remission induction.